Pengaruh Digital Citizenship terhadap Karakter Murid di Era Artificial Intelligence: Indonesia - Eries Maulita Aisyah; Silvia Vidia Wati (Global Education Journal, 2026)
The rapid advancement of Artificial Intelligence (AI) has transformed educational practices while creating new challenges for students' character development. In this context, digital citizenship has become an essential competency that enables students to use digital technology ethically, responsibly, and critically. This study aims to analyze the influence of digital citizenship on students' character in the AI era and to develop a conceptual synthesis of the relationship between AI, digital citizenship, and character education. A qualitative approach was employed using the Systematic Literature Review (SLR) method based on the Kitchenham framework. Ten scientific articles published between 2021 and 2026 were selected through predefined inclusion and exclusion criteria and analyzed using content analysis. The findings indicate that digital citizenship is the primary factor supporting students' character development through digital literacy, digital ethics, responsibility, and critical thinking. These competencies contribute to the development of honesty, integrity, empathy, social responsibility, and respect for others. Although AI enhances learning effectiveness, creativity, adaptive learning, and assessment, its misuse may lead to plagiarism, misinformation, technology dependence, and reduced academic integrity. This study concludes that AI does not directly shape students' character; instead, its influence is mediated by digital citizenship. Therefore, integrating digital citizenship into curriculum and learning practices is essential for fostering ethical, responsible, and digitally competent students.